Bioremediation of heavy metals from wastewater: a current perspective on microalgae‐based future. (4th October 2021) - Goswami, R.K.; Agrawal, K.; Shah, M.P.; Verma, P.
Abstract: Heavy metals‐containing drinking water and wastewater are posing a severe threat to the environment, and living beings on land, air and water. Different conventional, advanced nanomaterials‐based and biological method has been employed for the treatment of heavy metals. Among the biological methods, microalgae are an important group of micro‐organisms that have numerous environmental applications and can remediate heavy metals from wastewater. Also, it has numerous advantages over conventional remediation processes. Microalgae cells can uptake the heavy metal via different physiological and biological methods and are utilized as a nutrient source to regulate its metabolic process for the production of biomass. Furthermore, the enhancement in heavy metal removal efficiency can be improved using different strategies such as immobilization of algal cells, development of algal consortia and designing of microalgae‐based nanocomposite materials. Also, it can significantly contribute towards environmental sustainability and future. Thus, the review provides a critical overview of heavy metals and their existence along with their negative effects on humans. This review provides insight on recent advanced nanomaterial approaches for the removal of heavy metals, overviews of microalgae‐based heavy metal uptake mechanisms and their potential for the amputation of different heavy metals. Furthermore, the special focus is on recent strategies that enhance heavy metal removal efficiency and contribute towards sustainability for the development of a microalgae‐based future. Abstract : Significance and Impact of the Study: The presence of heavy metals in water can cause serious health implications for human beings. Thus, microalgae‐based heavy metals bioremediation is considered as a possible solution for resolving current environmental problems and has been critically discussed in the present review. Also, it can use different mechanisms for the uptake of heavy metals and their recovery efficiencies are discussed. The present review also discusses recent strategies involved in the microalgal‐based heavy metal bioremediation process. It would further enable us to bridge the gap between the green‐sustainable approach to overcome environmental issues and the development of a microalgae‐based future.